Trajectory of local farmers on the institutional change level of agricultural land in the agrotourism zone: (Study on institutional change of agricultural in Indonesia) - Rozuli, Ahmad Imron (Technium Social Sciences Journal, 2020)
The research offers a thesis to view the context of land institutional change of agriculture as a factor in local farmer identity formation. The goal is to reject the general idea that always presents a thesis that the change of land institutional has always had a bad impact for farmers. To achieve the research objectives, researchers used Giddens concept the Trajectory of Self, using qualitative methods and phenomenological approaches. This research is focused on the region of Agrotourism in Indonesia, with the technique of observation data collection, in-depth interview, Transect Walk, focus group discussion (FGD), as well as secondary data analysis. The results showed that Dutch colonialization in agriculture became the first phase creation of modernity on land, as land. This condition, which formed a self-development of local farmers, is unconsciously organized and reflective on globalization flows. Thus, creating an institutional that is reversible time, which is a long term and reversible conditioning in spacetime In the form of social activities that are patterned in continuity of daily living and then form the identity of local farmers.